Konsep Karakter dalam Kitab Taysir Al-Khallaq dan Relevansinya dengan Permendikbud No. 20 Tahun 2018 - Rizqiyah, Afi; Thobroni, Ahmad Yusam; Syamsudin (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2023)
Character is an important element in the progress of a nation’s civilization. The term character was initially introduced by the Western world. But actually in Islam, character has been studied by Muslim intellectuals with the term akhlak. The book of morals is still used as a learning resource in pesantren as a support for character education. So that problems arise regarding the fulfillment of national character education standards through character education from these books. Departing from this background, this study aims to examine the relevance of the concept of character in the book of Taysir al-Khallaq with Permendikbud No. 20/2018. The research was conducted using the literature method with a qualitative approach. The data were analyzed using typology analysis techniques. The results showed that there were 31 character values in the book of Taysir al-Khallaq which included morals towards Allah SWT, morals towards self, morals towards others, praiseworthy traits, and telrcella traits. Meanwhile, Permendikbud No. 20 of 2018 stipulates 18 character values that are based on aspects of religion, Pancasila, buldaya, and national education goals. After the character values from the two research objects were analyzed for linguistic and conceptual relevance, 12 relevant character values were found. Based on the results of this analysis, the concept of character in the book of Taysir al-Khallaq is relevant to Permendikbud No. 20/2018. So character education in the Taysir al-Khallaq book meets the national character education standards and is suitable as a learning resource to support character education in pesantren that use it in their internal curriculum.